2002
DOI: 10.3732/ajb.89.5.777
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome‐specific desynapsis in the n = 2 race of Haplopappus gracilis (Compositae)

Abstract: During cytological screening for pollen sterility in a wild population of Haplopappus gracilis (n = 2), several partially sterile plants were found that had good pachytene pairing but varying numbers of univalents. Some plants had chromosome A bivalents or A univalents, while in the same cells chromosome B had only bivalents. In other plants the reverse condition occurred; the B chromosome had B bivalents or B univalents and only A bivalents. This demonstrates a chromosome-specific effect for the desynapsis ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…This phenomenon has been reported in many species such as Oenothera (Catcheside 1939), Cyamopsis tetragonoloba (Sahoo and Gill 1975), Cistanche tubulosa (Batia and Uzi 1995), Lolium perenne (Omara and Hayward 1978) and other species (Christopher 1971, Datta and Biswas 1985, Poddar et al 1998, Sengupta et al 1999, Saha and Datta 2002. Besides this, some members of Asteraceae, such as Haplopappus gracilis (Jackson et al 2002) and Crepis (Richardson 1935) show this phenomenon. Failure of chromosome pairing may be due to chromosome-specific desynapsis due to a single recessive gene or it may be generalized, affecting the whole genome.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon has been reported in many species such as Oenothera (Catcheside 1939), Cyamopsis tetragonoloba (Sahoo and Gill 1975), Cistanche tubulosa (Batia and Uzi 1995), Lolium perenne (Omara and Hayward 1978) and other species (Christopher 1971, Datta and Biswas 1985, Poddar et al 1998, Sengupta et al 1999, Saha and Datta 2002. Besides this, some members of Asteraceae, such as Haplopappus gracilis (Jackson et al 2002) and Crepis (Richardson 1935) show this phenomenon. Failure of chromosome pairing may be due to chromosome-specific desynapsis due to a single recessive gene or it may be generalized, affecting the whole genome.…”
mentioning
confidence: 99%
“…Failure of chromosome pairing may be due to chromosome-specific desynapsis due to a single recessive gene or it may be generalized, affecting the whole genome. The desynaptic genes in the tomato are examples of hologenomic mutations that affects all bivalents (Jackson 1985) and chromosome-specific desynapsis that affect single bivalents is reported in species of Haplopappus, Crepis and Hypochoeris. Cohesin is a gene that is responsible for the cohesion of sister chromatids together.…”
mentioning
confidence: 99%
“…Peirson et al (1996) suggested that the mutation may disrupt the early stage of meiosis and results in the formation of aberrant microsporocytes and megasporocytes. Research on desynaptic mutants continues in many economically important plants but primarily used as a source of trisomics for genetic analysis (Jackson et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic factors present on single chromosomes that affect genome-wide recombination frequency have recently been found in Brassica (Suay et al, 2014). However, genetic factors influencing recombination between particular chromosomes have yet to be identified in the Brassica genus, although chromosome-specific genetic factors have been identified in other species (Jackson et al, 2002). Hence, certain chromosomes or chromosome pairs (e.g.…”
Section: Molecular Karyotyping Predicts Segregation Between Regions Omentioning
confidence: 99%